When Daddy prays - Grimes, Nikki; Ladwig, Tim (Grand Rapids. Mich. : Eerdmans Books for Young Readers, 2002)
In this collection of poems, a child expresses love and affection for Daddy and reflects on the many times Daddy talks to God.
In this collection of poems, a child expresses love and affection for Daddy and reflects on the many times Daddy talks to God.
Keywords: Fathers -- Juvenile poetry; Children's poetry, American; Christian poetry, American; Prayer -- Juvenile poetry; Fathers -- Poetry; Prayer -- Poetry; Christian life -- Poetry; African Americans -- Poetry; American poetry